Moving with my Story : exploring the relationship between Narrative Identity and the Bodily Self in Depersonalization Experiences - Colombo, Alberto (2023)
Tese de Mestrado, Ciência Cognitiva, 2024, Universidade de Lisboa, Faculdade de Ciências